Batch and Continuous Ultrasound Assisted Extraction of Boldo Leaves (Peumus boldus Mol.) - Joël Wajsman (International Journal of Molecular Sciences, 2013)
Vegetal extracts are widely used as primary ingredients for various products from creams to perfumes in the pharmaceutical, nutraceutic and cosmetic industries. Having concentrated and active extract is essential, as the process must extract as much soluble material as possible in a minimum time, using the least possible volume of solvent. The boldo leaves extract is of great interest for the industry as it holds a great anti-oxidant activity due to high levels of flavonoids and alkaloids such as boldine. Ultrasound Assisted Extraction (UAE) has been used to improve the efficiency of the plant extraction, reducing extraction time, increasing the concentration of the extract with the same amount of solvent and plant material. After a preliminary study, a response surface method has been used to optimize the extraction of soluble material from the plant. The results provided by the statistical analysis revealed that the optimized conditions were: sonication power 23 W/cm2 for 40 min and a temperature of 36 °C. The optimized parameters of the UAE provide a better extraction compared to a conventional maceration in terms of process time (30 min instead of 120 min), higher yield, more energy saving, cleanliness, safety and product quality.